AB0461 Experience with subcutaneous abatacept in routine clinical practice: 6-month interim analysis of a 2-year, prospective, non-interventional, multicentre study in patients with ra. (12th June 2018) - Alten, R.; Mariette, X.; Buch, M.; Caporali, R.; Flipo, R.-M.; Forster, A.; Griffiths, H.; Nurmohamed, M.; Patel, Y.; Peichl, P.; Sanmarti, R.; Chauvet, C.; et al.
Abstract : Background: ASCORE (Abatacept SubCutaneOus in Routine clinical practicE; NCT02090556 ) is an ongoing, prospective, non-interventional, multicentre study of patients (pts) with RA receiving SC abatacept (ABA). In a similar real-world setting, IV ABA retention was >88% at 6 months (M). 1 Objectives: To present baseline (BL) pt characteristics and 6M interim retention rates and clinical outcomes for SC ABA by biologic (b)DMARD treatment line. Methods: Pts (≥18 years) with active, moderate-to-severe RA, naïve to ABA and who initiated SC ABA 125 mg weekly were enrolled across 10 countries (March 2013–January 2017) in 2 cohorts: biologic-naïve pts and pts who had failed ≥1 prior bDMARD. In some countries, an IV loading dose was administered according to local practice. Pt demographics and disease characteristics at SC ABA initiation were recorded. The retention rate (95% CI) of SC ABA over 6M was estimated by Kaplan–Meier analysis. Good/moderate EULAR response rates based on DAS28 (ESR, otherwise CRP), low disease activity (LDA) or remission according to DAS28 (ESR), CDAI, SDAI and Boolean criteria were assessed at 6M. Results: Of 2943 pts enrolled, 2785 (94.6%) were evaluable: 1155 (41.5%) biologic naïve; 718 (25.8%) had failed 1; and 912 (32.7%) had failed ≥2 prior biologics. At BL, there was a higher proportion of females and pts with longer disease duration among those who had failed ≥2 vs 1 or no prior bDMARDs; disease activity was similar across treatment lines; CRP was higher in biologic-naïve vs -failure pts; 402 (48.4%) biologic-naïve pts had erosive disease vs 261 (53.7%) or 390 (63.8%) who had received 1 or ≥2 prior bDMARDs, respectively. Probability of overall SC ABA retention at 6M was 0.88 (95% CI 0.86, 0.89); retention was higher in pts receiving ABA as a first or second vs later bDMARD (figure 1). At 6M, 335 pts had discontinued ABA, 172 (51.3%) of whom due to inefficacy and 140 (41.8%) due to safety. At 6M, among pts continuing ABA, good/moderate EULAR response rates were 83.5%, 75.1% and 72.0% for biologic-naïve pts and pts with 1 and ≥2 prior bDMARD failures, respectively. DAS28 (ESR), CDAI or SDAI LDA/remission, or Boolean remission rates were higher with earlier vs later treatment lines. The safety profile was consistent with IV ABA studies. 1, 2 Conclusions: In this first observation of SC abatacept in a real-world setting, overall retention of SC abatacept at 6M was high and similar to that observed with IV abatacept. 1 Better retention and response rates were achieved with abatacept as an earlier bDMARD treatment line. Good/moderate EULAR response rates at 6M were consistently >70%, irrespective of treatment line and higher BL radiographic erosion in biologic-failure pts. References: [1] Nüßlein HG, et al. BMC Musculoskelet Disord2014;15:14. [2] Nüßlein HG, et al. Clin Exp Rheumatol2016;34:489–99. Disclosure of Interest: R. Alten Grant/research support from: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb, X. Mariette Grant/research support from: Biogen, Pfizer, UCB, Speakers bureau: Bristol-Myers Squibb, LFB, GSK, Pfizer, UCB, M. Buch Grant/research support from: AbbVie, AstraZeneca, Eli Lilly, Pfizer, Roche, Sandoz, UCB, Consultant for: AbbVie, AstraZeneca, Eli Lilly, Pfizer, Roche, Sandoz, UCB, R. Caporali Speakers bureau: Bristol-Myers Squibb, AbbVie, Celgene, Eli Lilly, MSD, Pfizer, Roche, UCB, R.-M. Flipo Consultant for: Bristol-Myers Squibb, A. Forster Consultant for: AbbVie, Bristol-Myers Squibb, Pfizer, Celgene, Roche, Novartis, UCB Pharma, Speakers bureau: AbbVie, Bristol-Myers Squibb, Pfizer, Celgene, Roche, Novartis, UCB Pharma, H. Griffiths Grant/research support from: AbbVie, Janssen, and Sanofi, Consultant for: Bristol-Myers Squibb and Janssen, Paid instructor for: Novartis, M. Nurmohamed Grant/research support from: Pfizer, AbbVie, Roche, Bristol-Myers Squibb, MSD, Mundipharma, UCB, Janssen, Menarini, Eli Lilly, Sanofi, Celgene, Consultant for: Pfizer, AbbVie, Roche, Bristol-Myers Squibb, MSD, Mundipharma, UCB, Janssen, Menarini, Eli Lilly, Sanofi, Celgene, Speakers bureau: Pfizer, AbbVie, Roche, Bristol-Myers Squibb, MSD, Mundipharma, UCB, Janssen, Menarini, Eli Lilly, Sanofi, Celgene, Y. Patel Grant/research support from: Bristol-Myers Squibb, Pfizer, AbbVie, Speakers bureau: Bristol-Myers Squibb, Pfizer, AbbVie, P. Peichl Consultant for: Bristol-Myers Squibb, Eli Lilly, R. Sanmarti Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, C. Chauvet Employee of: Bristol-Myers Squibb, J. Heitzman Employee of: Bristol-Myers Squibb, C. Rauch Employee of: Bristol-Myers Squibb, S. Connolly Employee of: Bristol-Myers Squibb